2013
DOI: 10.13172/2052-0069-2-2-713
|View full text |Cite
|
Sign up to set email alerts
|

Preanalytical variables and factors that interfere with the biochemical parameters: A review

Abstract: IntroductionThe total testing process, which begins with the order of the physician, includes the preanalytical, analytical and postanalytical phases and ends with the results ready for interpretation. To obtain a reliable test result requires detection of all steps however, to control the preanalytical stage is such a complex way that much of the steps are human dependent and out of the laboratory's control thus occupies the most erroneous part of the total testing. The worst side is that the error in that st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
0
18
0
2
Order By: Relevance
“…Notably, our achievement in stabilizing surface marker expression and blood counts for up to 72 h surpasses the recommended storage duration set by the WHO by three- and sixfold, respectively 47 . The impact of these results on healthcare is significant; an estimated 46–68.2% of errors in laboratory testing are associated with the pre-analytical phase 48 , in which inadequate sample collection, handling, transportation, and storage are thought to be the major contributors to error 49 . Indeed, it has been reported that up to 54% of missing test results can be attributed to hemolysis alone 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, our achievement in stabilizing surface marker expression and blood counts for up to 72 h surpasses the recommended storage duration set by the WHO by three- and sixfold, respectively 47 . The impact of these results on healthcare is significant; an estimated 46–68.2% of errors in laboratory testing are associated with the pre-analytical phase 48 , in which inadequate sample collection, handling, transportation, and storage are thought to be the major contributors to error 49 . Indeed, it has been reported that up to 54% of missing test results can be attributed to hemolysis alone 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, untrained hospital staff (uneducated or have less than high school degrees) were transporting the samples. Studies showed that staff and trained phlebotomists make 2–4 times fewer pre-analytical errors than non-phlebotomists and lab staff [10]. A separate study showed that general practitioners and clinical hospital wards made about half of the pre-analytical errors [7].…”
Section: Discussionmentioning
confidence: 99%
“…Jaffé reaction may also be affected by lipemia and/or haemolysis. Haemolysed samples that contain fetal haemoglobin (HbF) interfere with the Jaffé reaction, and it is possible to obtain negative creatinine results ( 24 ). Management of lipemic samples was extensively explained in the review by Nikolac et al ( 25 ).…”
Section: Creatininementioning
confidence: 99%